In vitro cytotoxicity assessment of the 3D printed polymer based epoxy resin intended for use in dentistry - Puškar, Tatjana; Trifković, Branka; Djurović Koprivica, Daniela; Kojić, Vesna; Jevremović, Ana; Mirković, Siniša; Eggbeer, Dominic (Vojnosanitetski pregled, 2021)
Background/Aim. There is limited published evidence on the cytotoxicity of 3D printed polymer materials for dentistry applications, despite that they are now widely used in medicine. Stereolithography (SLA) is one of the foremost 3D processes used in 3D printing, yet there are only a small number of resin materials reported to be suitable for medical applications. The aim of this study was to investigate, in vitro, the cytotoxic effect of the 3D printed resin in order to establish the suitability for its usage in dentistry and related medical applications such as surgical dental guides, occlusal splits and orthodontic devices. Methods. To examine the cytotoxicity of the 3D printed polymer-based epoxy resin, Accura® ClearVue™ (3D-Systems, USA), two cell cultures were used: mouse fibroblasts L929, and human lung fibroblasts MRC-5. The cell viability was determined by the Mosmann’s colorimetric (MTT) test and the agar diffusion test (ADT). Results. Direct contact of the tested material with the ADT test showed nontoxic effects of tested material in any cell culture. The tested material showed no cytotoxic effect after 3 days of extraction of the eluate by the MTT, but mild cytotoxic effect after 5, 7 and 21 days on both cell lines. The cytotoxicity increased with increasing the time of the eluate extraction. Conclusion. The 3D printed polymer-based epoxy resin, Accura® ClearVue™ (3D-Systems, USA) is considered appropriate for making surgical dental implant guides according to the cytotoxic behavior. According to the mild level of cytotoxicity after the longer extraction periods, there is a need for further evaluation of biocompatibility for its application for the occlusal splints and orthodontic devices.